Pengaruh Budaya Organisasi Terhadap Keterlibatan Karyawan Perusahaan di Era Globalisasi - Daryoto Mulyadi Candra (Institut Nalanda, 2024)
Whether the flow of globalization is realized or not is able to have a significant influence on the behavior, skills and emotional relationships of workers or employees towards the place where they work or the company. Apart from that, the existence and behavior of organizational culture is also no less competitive in providing encouragement and changes in an employee's attitude, mindset and work ethic towards the company where he works. So that these two things, organizations and the flow of globalization must be able and able to be handled well so that the relationship between employees and the company can still be maintained well and will actually be able to have a positive influence on the development of the company which is supported by advances in technology and work skills. Thus, the results of this research show that a good organizational culture and building good relationships with employees in the era of globalization will be able to encourage the progress of the company and the development of employee work ethics.